La Structure Institutionnelle de la Bancassurance en Algérie: Historique et Actualité - Guemmaz, Souhil (جامعة زيان عاشور بالجلفة, 2021)
This study aims to analyze the institutional structure of banc assurance in Algeria, established since 2008, after a series of preparations of a legal nature, essentially aiming at the construction of a structure including this new technique launched by the banker. The analysis of the institutional structure of Algerian banc assurance shows that banks in Algeria have opted for participation in the life branch to the detriment of damage. In addition, we argue that the institutional architecture of Algerian banc assurance encompasses at the same time all the models existing in the world, namely the distribution agreement, joint venture in public capital and full integration.
Keywords: قطاع التأمين -- التأمين المصرفي -- الجزائر